2013
DOI: 10.1128/jvi.02534-12
|View full text |Cite
|
Sign up to set email alerts
|

Low Oxygen Tension Enhances Hepatitis C Virus Replication

Abstract: ; Applied Molecular Virology, Institut Pasteur Korea, Seongnam-si, South Korea g Low oxygen tension exerts a significant effect on the replication of several DNA and RNA viruses in cultured cells. In vitro propagation of hepatitis C virus (HCV) has thus far been studied under atmospheric oxygen levels despite the fact that the liver tissue microenvironment is hypoxic. In this study, we investigated the efficiency of HCV production in actively dividing or differentiating human hepatoma cells cultured under low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 87 publications
4
62
0
Order By: Relevance
“…This implies that CKB might become upregulated under such conditions. To our knowledge, such upregulation has not been noted previously in cells infected with enteroviruses, although it has been reported that CKB is required for the replication of certain strains of hepatitis C, another positive-strand RNA virus [25,26]. Thus, it seems possible that CKB might play a hitherto unrecognised role in the development of a sustained infection of islet cells.…”
Section: Discussionmentioning
confidence: 58%
“…This implies that CKB might become upregulated under such conditions. To our knowledge, such upregulation has not been noted previously in cells infected with enteroviruses, although it has been reported that CKB is required for the replication of certain strains of hepatitis C, another positive-strand RNA virus [25,26]. Thus, it seems possible that CKB might play a hitherto unrecognised role in the development of a sustained infection of islet cells.…”
Section: Discussionmentioning
confidence: 58%
“…It has been shown that hypoxic conditions enhance HCV replication (12). We analyzed HCV infection in Huh7.5 cells under hypoxic conditions and observed increased infectivity of JFH1 (HCVcc JFH1 ), an infectious HCV clone (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Recent studies have demonstrated that HCV RNA replication in Huh7.5 cells is enhanced under hypoxic conditions (12). Because the oxygen content in liver tissue in vivo is estimated to be lower (with a gradient of 9-3%) than the oxygen content under in vitro culture conditions (13), the HCV life cycle may differ significantly from that observed using in vitro culture systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…in Huh7.5 cells, which was associated with increased activity of anaerobic cell energy production and proliferation (59). Thus, the interplay between hypoxia-induced stemness and cell energy machinery activation by HCV, and through that enhancement of HCV replication, may promote HCV spread and tumorigenesis in chronically infected individuals (60).…”
Section: Discussionmentioning
confidence: 99%